Impact of the Hole Transport Layer on the Charge Extraction of Ruddlesden–Popper Perovskite Solar Cells - Wang, Qingqian (ACS Appl Mater Interfaces, 2020)
[Image: see text] Recent works demonstrate that polyelectrolytes as a hole transport layer (HTL) offers superior performance in Ruddlesden–Popper perovskite solar cells (RPPSCs) compared to poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS). The factors contributing to such improvement need to be systematically investigated. To achieve this, we have systematically investigated how the two HTLs affect the morphology, crystallinity, and orientation of the Ruddlesden–Popper perovskite (RPP) films as well as the charge extraction of the RPPSCs. PEDOT:PSS as a HTL leads to RPP films of low crystallinity and with a number of large pinholes. These factors lead to poor charge carrier extraction and significant charge recombination in the RPPSCs. Conversely, a PCP-Na HTL gives rise to highly crystalline and pinhole-free RPPSC films. Moreover, a PCP-Na HTL provides a better energy alignment at the perovskite/HTL interface because of its higher work function compared to PEDOT:PSS. Consequently, devices using PCP-Na as HTLs are more efficient in extracting charge carriers.